Analysis Quality Dino Tour Travel Management Website Using WebQual 4.0 - Rola Hengki (International Conference on Engineering and Technology Development (ICETD), 2014)
The rapid development of internet technology is getting a lot of benefits, especially in the use of the website. Therefore, an aspect of the website must meet the standards of quality websites. In this study, the quality of the Dino Tour Travel Management website is measured by using the WebQual method. WebQual is one method or technique of measuring the quality of a website based on the perception of the end user. This method is an extension of the widely used SERVQUAL prior to the measurement of service quality. From the analysis and the results of a questionnaire distributed to 23 respondents, it can be concluded that Dino Tour Travel Management website (pulautidungdino.com) meets a standard aspect of quality websites based WebQual 4.0. However, the low value of the acquisition for some questions, the manager of the website are advised to provide information that is more detailed and easy to understand.